Forecasting Model of Ice Poci Tea Sales with Linear Regression Algorithm and Determination of Reorder Point Using Safety Stock and Reorder Point Methods: Model Peramalan Penjualan Teh Poci dengan Algoritma Linear Regression dan Penentuan Reorder Point Menggunakan Metode Safety Stock dan Reorder Point - Kurniawati, Devi Riskhi; Nuryana, I Kadek Dwi (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2024)
Franchising is a form of cooperation between business owners and other parties with certain terms and conditions. Poci Iced Tea in Widodaren sub-district is one of the franchised businesses. However, this business often experiences problems in its business, especially the problem of controlling raw materials. Problems in business related to inventory control are shortages or excess inventory which leads to increased storage costs. To avoid these problems, it can be done by forecasting sales. In this study, the authors used the Linear Regression algorithm to create a sales forecasting model for iced tea pots. Researchers conducted a collection to obtain historical data based on the required variables, namely the number of sales of jasmine and vanilla variants of iced tea, rainfall, days, and ice cube usage. The results of this study obtained that the Iced Tea Poci Shop needs to prepare a Safety Stock of 48 pcs of jasmine variant tea, or each type of 16 pcs; and as many as 25 pcs of vanilla variant tea; and as many as 6 ball cups of 16oz teapots, for safety raw materials in case of unexpected sales. The Iced Tea Poci shop needs to reorder raw materials if there are 243 pcs of jasmine variant tea left or 81 pcs of each type left, a total of 3,900 pcs or 1,300 pcs for each type of tea; and if there are 88 pcs of vanilla variant tea left, a total of 1,275 pcs of tea, and if there are 28 balls left, a total of 431 balls of 16oz teacups.